An interdisciplinary approach to characterize peanut‐allergic patients—First data from the FOOD@ consortium. Issue 10 (5th October 2022) - Worm, Margitta; Alexiou, Aikaterina; Höfer, Veronika; Birkner, Till; Jeanrenaud, Alexander C. S. N.; Fauchère, Florent; Pazur, Kristijan; Steinert, Carolin; Arnau‐Soler, Aleix; Banerjee, Priyanka; Diefenbach, Andreas; Dobbertin‐Welsch, Josefine; et al.
Abstract : Background: Peanut allergy is a frequent cause of food allergy and potentially life‐threatening. Within this interdisciplinary research approach, we aim to unravel the complex mechanisms of peanut allergy. As a first step were applied in an exploratory manner the analysis of peanut allergic versus non‐allergic controls. Methods: Biosamples were studied regarding DNA methylation signatures, gut microbiome, adaptive and innate immune cell populations, soluble signaling molecules and allergen‐reactive antibody specificities. We applied a scalable systems medicine computational workflow to the assembled data. Results: We identified combined cellular and soluble biomarker signatures that stratify donors into peanut‐allergic and non‐allergic with high specificity. DNA methylation profiling revealed various genes of interest and stool microbiota differences in bacteria abundances. Conclusion: By extending our findings to a larger set of patients (e.g., children vs. adults), we will establish predictors for food allergy and tolerance and translate these as for example, indicators for interventional studies.